Peculiarities of Dental Treatment among Paediatric Oncological Patients: a Case Report - Egle Aida Bendoraitiene; Vilija Andruskeviciene; Gabriele Kscenaviciute; Evelina Srebaliene; Ieva Maciulaityte (eJournal of Oral Maxillofacial Research, 2020)
Objectives: According to the National Cancer Institute of Lithuania, cancer is diagnosed for almost 100 children each year. Oncological patients suffer from complications during and after treatment. Radiation therapy also affects dental hard tissues. Many oncological patients lose motivation to take care of their oral hygiene because they are focused on cancer diagnosis. This case report discusses prevention and dental treatment severity after radiation therapy treatment.